Analysis of the Effectiveness of General Services Retribution Revenue and Its Contribution to Local Revenue of Mataram City - M. Alif Husain; Abdul Manan; Eka Agustiani; Gaghman , AbdulGhani (Tinta Emas Publisher, 2024)
This study aims to analyze the growth rate and effectiveness of general service levy revenue, the contribution of general service levies to local retribution, and the contribution of both general service levies and local retribution to the Local Revenue (PAD) of Mataram City from 2018 to 2022. This research employs a quantitative descriptive approach. The analysis revealed that the growth rate of the general service levy in Mataram City between 2019 and 2022 showed positive growth, but the increase was minimal, with an average growth rate of only 13.86% (categorized as Unsuccessful). The effectiveness ratio of general service levy revenue from 2018-2022 averaged 61.53%, indicating a